2019
DOI: 10.3390/agriculture9100218
|View full text |Cite
|
Sign up to set email alerts
|

Conflicts of Interests When Connecting Agricultural Advisory Services with Agri-Input Businesses

Abstract: Conflicts of interests have been hypothesized when agricultural advisory services are connected to agri-input businesses. However, these have not been examined using large sets of advisory service and grower data. We provide quantitative insights into dependencies between service, crop production, sustainability and the level of agri-input business-linkage of extension workers. We analyzed 34,000+ prescription forms (recommendations) issued to growers in China, as well as grower interview data. Results reveale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 9 publications
1
12
0
Order By: Relevance
“…Literature that describes contemporary use of antibiotics on plants is usually confined to that of extension literature (https ://exten sion.psu.edu/pear-disea se-fire-bligh t), or reporting concerns over the development of antibiotic resistance in populations of plant pathogens (Sundin and Wang 2018;Farfán et al 2014). Exceptions to this are two recent papers from China that provide some insights into antibiotics being recommended by extension services in the country (Zhang et al 2017;Wan et al 2019). These papers use information derived from plant clinics in China and suggest that antibiotics appear in between 2.5 and 4.5% of the recommendations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Literature that describes contemporary use of antibiotics on plants is usually confined to that of extension literature (https ://exten sion.psu.edu/pear-disea se-fire-bligh t), or reporting concerns over the development of antibiotic resistance in populations of plant pathogens (Sundin and Wang 2018;Farfán et al 2014). Exceptions to this are two recent papers from China that provide some insights into antibiotics being recommended by extension services in the country (Zhang et al 2017;Wan et al 2019). These papers use information derived from plant clinics in China and suggest that antibiotics appear in between 2.5 and 4.5% of the recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…There are reports of other antibiotics being used in agriculture, such as gentamicin in Mexico and Costa Rica, oxonilic acid in Israel and kasugamycin in Japan and other Asian countries. However, with minor exceptions, (Rodríguez Sánchez 2008;Zhang et al 2017;Wan et al 2019) there are very limited data available on the extent of their use, on which crops and problems they are used against.…”
Section: Open Accessmentioning
confidence: 99%
“…More toxic/longer residual pesticides were not allowed to be prescribed in 2018. As for the 2015-2017 data, farmer surveys conducted in 2016 revealed that more than 90% of the plant protection recommendations on the plant clinic prescriptions were accepted and implemented by the farmers (Wan et al, 2019). Therefore, we assume that changes in the advice given by plant doctors, following the pesticide policy of China and subsidies by the local government, indeed led to a reduction in pesticide use.…”
Section: Impact: Pesticides Reduced and Ipm-compatible Pest Control Amentioning
confidence: 99%
“…In a complementary study most growers visited a plant doctor about once a month (i.e. 13 ± 12 times/year; Wan et al, 2019).…”
Section: Farmers Reachedmentioning
confidence: 99%
See 1 more Smart Citation